Preparation and crossing of basidiospore-derived monokaryons--a useful tool for obtaining laccase and other ligninolytic enzyme higher-producing dikaryotic strains of Pleurotus ostreatus - Eichlerová, I; Homolka, L (Antonie van Leeuwenhoek, 1999)
Laccase and other ligninolytic enzyme higher-producing dikaryons of Pleurotus ostreatus were obtained after crossing of compatible basidiospore-derived monokaryons selected from the parental basidiospore population on the basis of exceptionality in enzyme production, mycelium extension rate and/or colony morphology. As all detected changes in enzyme activity, mycelium extension rate, colony appearance and degradation of the polymeric dye Poly B411 were relatively stable after repeated testing, the dikaryotic isolates prepared in this way seem to be useful for the future biotechnological exploitation. No correlation between the colony appearance or the mating type and the enzyme activity or other characteristics tested has been found.
Keywords: lakasa; počet mikrobiálních kolonií; Laccase; spory hub; Colony Count, Microbial; křížení genetické; Spores, Fungal; lignin; Pleurotus; Lignin; Oxidoreductases; Crosses, Genetic; oxidoreduktasy